2009
DOI: 10.1002/cb.281
|View full text |Cite
|
Sign up to set email alerts
|

Noneconomic goals of investors

Abstract: This study adopts a consumer perspective and explores investors' noneconomic goals. This approach shifts the focus from the investment vehicle and its performance to the investor and her/his investing goals. We explore the influence of religiosity, environmental attitude, materialism, collectivism, risk tolerance, and social investing efficacy on investors' noneconomic goals. We find that social investing efficacy mediates the relationships between the aforementioned variables and noneconomic goals. Implicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 47 publications
2
29
1
1
Order By: Relevance
“…For example, Iyer and Kashyap (2009) report that investors emphasise more than just financial returns on investments, e.g. ''boycott firms deemed to be socially and environmentally responsible'', ''promote environmental causes'' and ''advance social agendas''.…”
Section: Theory and Hypothesismentioning
confidence: 98%
“…For example, Iyer and Kashyap (2009) report that investors emphasise more than just financial returns on investments, e.g. ''boycott firms deemed to be socially and environmentally responsible'', ''promote environmental causes'' and ''advance social agendas''.…”
Section: Theory and Hypothesismentioning
confidence: 98%
“…Traditional investors are extrinsically motivated by the prospect of future financial returns, while charitable donors are intrinsically motivated due to psychological gains. Iyer and Kashyap [25] explored the influence of materialism, social investment efficacy, risk tolerance, environmental attitude, collectivism, and religiosity on non-economic objectives of the investors. They concluded that investors would mix financial gains with their non-economic objectives, and sometimes investors are willing to forgo financial returns to achieve social benefits.…”
Section: Motivation Of Crowdfundersmentioning
confidence: 99%
“…Rosen et al . (), Lewis & Mackenzie (), McLachlan & Gardner (), Nilsson (), Williams (), Owen & Qian (), Starr (), Iyer & Kashyap (), Säve‐Söderbergh () use surveys; Webley et al . (), Pasewark & Riley () implement experiments; Renneboog et al .…”
unclassified